Penerapan Model Pembelajaran Mind Mapping Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Getaran dan Gelombang kelas VIII SMP Negeri 17 Halmahera Selatan - Ernawati Muhtar (Peneliti.net, 2022)
This research is a Classroom Action Research (CAR) which aims to improve the learning outcomes of Class VIII students on vibration and waves through the application of the Mind Mapping learning model at SMP Negeri 17 Halmahera Selatan. The subjects in this research were Class VIII students, totaling 30 students, consisting of 17 female students and 13 male students. From the results of this study it can be concluded that the application of the Mind Mapping learning model in improving student learning outcomes on vibration and waves material at SMP Negeri 17 Halmahera Selatan is very fulfilling. This can be seen from the initial conditions before the action on average the learning activities of students who complete was 57%, after the first cycle of research but had not experienced an increase in learning outcomes. The percentage of students in cycle I only reached 60%, and after conducting research in cycle II the percentage of students' completeness increased to 87%.